Etykietowanie uczniów w instytucjach edukacyjnych w Izraelu poprzez ich status ekonomiczny - Franco, Sali Manor (Studia Edukacyjne, 2016)
This paper shows that it is possible to note a number of points in the development of the educational system in Israel from the establishment of the State: the framework of uniform education from the end of 1948 until the conclusions of the Fromkin Committee in 1950 and the integration from 1968. The changes of policy reflect the historical changes that occurred in the social economic discourse and that shaped the development of the state of Israel. The system began its path as controlled by the center and as supporting social equality. After failed attempts to correct the difference that reigned between groups of students, reforms in the system, such as the implementation of the integration program, led to the presentation of a new policy, such as affirmative action. Following another failure, reforms were presented, and an attempt was made to return to the idea of equality through the presentation of analysis and evaluation related to the quality outputs of the system. Israel faces many challenges to improve its educational system, and it has the duty to persevere with the reforms it has initiated in the subject of education. Education is one of the most important investments that the State can make to improve its future.